2019
DOI: 10.1002/slct.201803032
|View full text |Cite
|
Sign up to set email alerts
|

Cluster‐like Co4N embedded into carbon sphere as an efficient, magnetic‐separated catalyst for catalytic hydrogenation

Abstract: The transition metal nitrides are promising catalyst in catalytic fields. The decrease of particle size is favourable to improve the catalytic ability, but its synthesis remains a challenge due to high calcination temperature in the synthesis. Here, we have reported the designed synthesis of cluster-like Co 4 N paticles (NPs) uniformly embedded in N-doped carbon microsphere (Co 4 N@NC) by controllable nitridation of a spherical Co-HQÀ S composed of Co 2 + and 8-hydroxy quinoline (8-HQ), and its used as efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…2b, the three binding energies at 779.14, 781.00, and 782.56 eV correspond to the Co-Co bond, Co-N bond, and Co-O bond, respectively. [31][32][33] Co-Co and Co-N bonds exist in the Co 4 N structure, while the Co-O bond is generated by the oxidation of the sample in air and in the Co-O-Ce bonds between Co 4 N and CeO 2 . It can be observed that after the formation of a heterostructure with CeO 2 , the binding energy corresponding to the Co-Co bond shows a tendency to move to a higher energy, showing electron loss in the Co 4 N. However, after the introduction of the plasma treatment, the binding energy clearly moved in a lower direction, showing an electron-accepting state.…”
Section: Resultsmentioning
confidence: 99%
“…2b, the three binding energies at 779.14, 781.00, and 782.56 eV correspond to the Co-Co bond, Co-N bond, and Co-O bond, respectively. [31][32][33] Co-Co and Co-N bonds exist in the Co 4 N structure, while the Co-O bond is generated by the oxidation of the sample in air and in the Co-O-Ce bonds between Co 4 N and CeO 2 . It can be observed that after the formation of a heterostructure with CeO 2 , the binding energy corresponding to the Co-Co bond shows a tendency to move to a higher energy, showing electron loss in the Co 4 N. However, after the introduction of the plasma treatment, the binding energy clearly moved in a lower direction, showing an electron-accepting state.…”
Section: Resultsmentioning
confidence: 99%
“…21 Co 4 N combined with carbon showed good activity for the hydrogenation of p -nitrophenol. 22–24 Through the construction of heterostructures, the catalytic performance can be further tuned based on the positive role of a heterointerface for optimizing the electronic structure. 25–30 The Co 2 N/Co showed improved performance for hydrogen electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…This allows these catalytic materials to meet the requirements for long periods under harsh reaction conditions. In addition, some late TMCs and TMNs have processed magnetic properties and can be recovered by external magnetic fields after being spent, 34,35 which makes them possess certain advantages in industrial catalysis. Despite these advantages, the application of transition metal carbide and nitride catalysts in the catalytic conversion of lignin and its model compounds is limited, especially for nitride.…”
Section: Introductionmentioning
confidence: 99%